2009
DOI: 10.1063/1.3153123
|View full text |Cite
|
Sign up to set email alerts
|

Reliable thin film encapsulation for organic light emitting diodes grown by low-temperature atomic layer deposition

Abstract: We report on highly efficient gas diffusion barriers for organic light emitting diodes (OLEDs). Nanolaminate (NL) structures composed of alternating Al2O3 and ZrO2 sublayers grown by atomic layer deposition at 80 °C are used to realize long-term stable OLED devices. While the brightness of phosphorescent p-i-n OLEDs sealed by a single Al2O3 layer drops to 85% of the initial luminance of 1000 cd/m2 after 1000 h of continuous operation, OLEDs encapsulated with the NL retain more than 95% of their brightness. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 17 publications
1
78
0
Order By: Relevance
“…2b is a schematic diagram of the Ca pad. With a normalized conductance vs time graph, the WVTR of the barrier can be calculated [16]. Fig.…”
Section: Fabrication and Wvtr Performance Of Hybrid Nano-stratified Mmentioning
confidence: 99%
See 1 more Smart Citation
“…2b is a schematic diagram of the Ca pad. With a normalized conductance vs time graph, the WVTR of the barrier can be calculated [16]. Fig.…”
Section: Fabrication and Wvtr Performance Of Hybrid Nano-stratified Mmentioning
confidence: 99%
“…This multi-barrier permeation mechanism has been discussed by Graff et al [15]. In contrast, the nanolaminate barrier just uses inorganic layers which are laminated by other kinds of inorganic materials on a nanoscale level [16]. Because of its excellent gas barrier property, it has a low WVTR at the same thickness of a single inorganic barrier [17].…”
Section: Introductionmentioning
confidence: 97%
“…A denser ZrAlxOyaluminate phase with higher packing density could be formed at the interfaces between Al 2 O 3 and ZrO 2 , leading to a densification at the Al 2 O 3 /ZrO 2 interfaces [18,19]. Because the permeation rate for gasses such as water vapor depends on the density of the material, even a small amount of water can enter into the device through the thin film.…”
Section: × 10mentioning
confidence: 99%
“…[7][8][9] It is therefore plausible to choose ALD to conformally cover of the particles responsible for the pinholes present on the cathode. Several studies have already shown that Al 2 O 3 synthesized by ALD is a promising candidate for OLED encapsulation, [10][11][12][13][14][15][16][17] however in these contributions the focus is on the engineering of barrier layers on polymer substrates. In the present work, we evaluate the inorganic barrier films in terms of intrinsic barrier performance as well as in terms of particle/defect conformal coverage a) Author to whom correspondence should be addressed; electronic mail: m.creatore@tue.nl 18 as described below.…”
Section: à2mentioning
confidence: 99%